Prehospital Airway Management in Emergency and Trauma Patients: A Cross-sectional Study of Ambulance Service Providers and Staff in a Low- and Middle-income Country. Issue 6 (12th November 2015) - Ismail, Samina; Zia, Nukhba; Samad, Khalid; Naeem, Rubaba; Ahmad, Haris; Raza, Amir; Baqir, Muhammad; Khan, Uzma Rahim
Abstract: Background: Prehospital airway management (AM) is the first priority in the care of emergency and trauma victims as it has shown to improve survival in these patients. Objective: The aim of this study was to assess training and knowledge of ambulance staff and availability of AM equipment in ambulances of Karachi, Pakistan. Methods: This cross-sectional study was conducted from June through September 2014. Interviews were conducted with management of six ambulance service providers and 165 ambulance staff. Data from the management included availability of AM equipment in the ambulances, number and designation of staff sent for emergency calls, and AM training of staff. Ambulance staff were assessed for their awareness, knowledge, and training pertaining to AM. Results: All the ambulance services (A through F) had basic equipment for AM but lacked qualified and trained staff. All services had solo drivers (98.3%) for emergency calls; however, Ambulance Service A also had doctors and paramedics. Only 35.7% (59/165) of ambulance staff had awareness regarding AM, out of which 77.9% (46/59) belonged to Ambulance Service A. Of these 59 staff, 81.4% received some form of AM training. Staff with AM awareness, when assessed for knowledge pertaining to AM steps and AM equipment, had a mean score of 4.7/5 and 8.4/12, respectively. Conclusion: Even though ambulances are equipped with basic equipment, due to lack of trained staff, these ambulances only serve the mere purpose of transportation. There is a need to train ambulance staff and increase ambulance to staff ratio to improve prehospital AM and patient survival. S Ismail, N Zia, K Samad, R Naeem, H Ahmad, A Raza, M Baqir, UR Khan .Prehospital airway management in emergency and trauma patients: a cross-sectional study of ambulance service providers and staff in a low- and middle-income country .Prehosp Disaster Med .2015 ;30 (6 ):606 –612 .